Hubungan antara Job Characteristic dengan Perilaku Cyberloafing pada Karyawan Tenaga Kependidikan Biro Akademik dan Kemahasiswaan di Universitas Andalas - Herio Rizki Dewinda; Syarifatul Hidni Rafli; Ria Okfrima (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
This study aims to determine the relationship between Job Characteristics and Cyberloafing Behavior among Educational Staff at the Academic and Student Affairs Bureau at Andalas University. The independent variable in this study is Job Characteristic and the dependent variable is Cyberloafing. The measuring instrument used in this study was saturated sampling technique. The sample in this study were 45 employees of the Academic and Student Affairs Bureau at Andalas University. Validity and reliability tests in this study used the Aplha Cronbach technique. The results of the validity coefficient on the Job characteristic scale move from rix = 0.347 to rix = 0.657 with a reliability coefficient of α = 0.843. Meanwhile, on the cyberloafing scale, it moves from rix = 0.331 to rix = 0.670 with a reliability coefficient of α = 0.898. Based on data analysis, the correlation value is 0.434 with a positive direction, with a significance level of 0.003, which means that the hypothesis is accepted. This shows that there is a significant positive relationship between job characteristics and cyberlaofing.